Effects of heat treatment of proportions of sorghum grain in fattening lamb rations - Menzies, C.S.; Richardson, D.; Deyoe, C.W.; Pfost, H.B. (Kansas Agricultural Experiment Station, 2011)
Research indicates that treating grains with heat may improve feedlot performance of ruminant animals. Previous work here indicated that treating all grain or roughage with heat resulted in reduced palatability. This test was designed to determine the effect of treating various proportions of th grain in the ration.
Keywords: Lamb; Sorghum grain; Protein; Alfalfa